2017
DOI: 10.1002/cbin.10752
|View full text |Cite
|
Sign up to set email alerts
|

Renal damage following Alloxan‐induced diabetes is associated with generation of reactive oxygen species, alterations of p53, TGF‐β1, and extracellular matrix metalloproteinases in rats

Abstract: Renal damage is a common problem in diabetes. Alloxan, a potent hyperglycemic and diabetogenic molecule, can induce diabetes through oxidative stress-related mechanisms. Here, we hypothesize that "Alloxan-induced renal damage is associated with alterations of p53, TGF-β1, and extracellular matrix metalloproteinases." To test our hypothesis, we established an animal model (male abino rats) and induced diabetes by intraperitoneal injection of Alloxan monohydrate. Rats with fasting blood glucose level ≥ 200 mg/dL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The abundance of matrix metalloproteinase-9 (MMP-9), an ECM-degradation MMP, was decreased in transgenic mice that overexpressed TGF-β1 (Zechel et al, 2002;Ueberham et al, 2003). In addition, TGF-β1 augmented the expression of tissue inhibitor of metalloproteinases-1 (Ueberham et al, 2003;Abdel Aziz et al, 2017), which inhibited the ECM-degrading MMPs.…”
Section: Tgf-β1 Promotes Renal Fibrosis In Dkdmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of matrix metalloproteinase-9 (MMP-9), an ECM-degradation MMP, was decreased in transgenic mice that overexpressed TGF-β1 (Zechel et al, 2002;Ueberham et al, 2003). In addition, TGF-β1 augmented the expression of tissue inhibitor of metalloproteinases-1 (Ueberham et al, 2003;Abdel Aziz et al, 2017), which inhibited the ECM-degrading MMPs.…”
Section: Tgf-β1 Promotes Renal Fibrosis In Dkdmentioning
confidence: 99%
“…Although sodium-glucose co-transporter 2 (SGLT2) inhibitors have conferred cardiovascular and renal protection (Perkovic et al, 2019), effective therapy for DKD is still unavailable. An epidemiological study revealed that the 5-year mortality rate of DKD was approximately 40%, as high as many cancers (Abdel Aziz et al, 2017). Transforming growth factor-β1 (TGF-β1) signaling contributes to DKD progression, and inhibiting TGF-β1 signaling has shown potential renoprotective properties in animal and human studies.…”
Section: Introductionmentioning
confidence: 99%
“…Unlikely to enalapril [74], insulin treatment ameliorated these changes [75]. MMP-1 expression and serum levels were also down-regulated in alloxan induced-diabetic mice [76,77], while local delivery of Mmp-1 into mice kidneys prevented diabetic renal fibrosis [78].…”
Section: Mmps In Experimental Diabetic Nephropathymentioning
confidence: 99%
“…Another experimental study with alloxan-induced diabetes in rodents was associated with low serum MMP-1 levels and increased levels of TIMP-1 expression in promoting kidney damage [31]. …”
Section: Collagenases (Mmp-1 Mmp-8 Mmp-13 and Mmp-18)mentioning
confidence: 99%